Rationality and Responsibilities: The Purpose of Critical Thinking - Henrysson, Henry Alexander (Menntavísindasvið Háskóla Íslands, 2016)
Substantial attention has been paid to the notion of critical thinking in Iceland in recent years, including within the national curricula. Amidst a certain confusion about the exact meaning of critical thinking, calls have surfaced for more emphasis on creative and positive thinking at the expense of critical elements. This paper asks whether critical skills are not in fact essential for constructive thinking and thus full of positive connotations. First, the argument is made that critical thinking has a necessary ethical dimension. Despite there being something fundamentally wrong with the idea that one can both be an evil character and a truly thoughtful person, this dimension is often overlooked. Some people fail to perform their duty to seek adequate justifications for their convictions, ignore the need to be critical when facing an ethical dilemma and place too much faith in their inner moral guides. Other people see no need to worry about temptations that follow one’s intellectual prowess. Neither group grasps how ethics and critical thinking are intertwined. This first point on the links between critical thinking and morality is followed by a discussion on what skills are the ingredients of critical thinking. The understanding of logical fallacies and the possession of analytical skills are obviously important, but there are other no less important questions one should ask oneself when forming a critical opinion. One has to grasp what exactly the topic is, why it is important to consider it, who is influencing whom in making certain judgements and what may result in having a specific conviction. In other words, critical thinking is to look at a certain issue from every possible angle, and thus the adjective ‘critical’ should not be confused with the verb ‘to criticise’, which has more obvious negative connotations. Drawing on this perspective, this paper points out why training in critical thinking should not solely focus on either debunking the opinions of others or on the various limits of the social ...